2005
DOI: 10.1097/01.ta.0000152498.71380.3e
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Comparison of the Selective Observation and Routine Exploration Methods for Penetrating Abdominal Stab Wounds With Organ or Omentum Evisceration

Abstract: The selective observation method is safe and superior to routine laparotomy for the treatment of penetrating abdominal stab wounds with omentum evisceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
58
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 26 publications
0
58
0
2
Order By: Relevance
“…In series where patients with penetrating injuries undergo routine explorative laparotomy, it has been shown that approxi- mately 30-50% of these patients do not actually require treatment (negative laparotomy) (21)(22)(23). In our study, the negative laparotomy rate was 28% and we believe this rate will decrease with more rigorous clinical and laboratory evaluation and perhaps with more effective use of diagnostic laparoscopy.…”
Section: Discussionmentioning
confidence: 60%
“…In series where patients with penetrating injuries undergo routine explorative laparotomy, it has been shown that approxi- mately 30-50% of these patients do not actually require treatment (negative laparotomy) (21)(22)(23). In our study, the negative laparotomy rate was 28% and we believe this rate will decrease with more rigorous clinical and laboratory evaluation and perhaps with more effective use of diagnostic laparoscopy.…”
Section: Discussionmentioning
confidence: 60%
“…The duration of hospitalization of 9 days of our patients does not differ from those found in the series varying between 5 and 9 days [23] [24].…”
Section: Comments-discussionmentioning
confidence: 60%
“…Операция при этом рассматривается и как диагностическая мани-пуляция, и как доступ для коррекции повреждений [14]. Но, как показывают многочисленные сообще-ния, проникающие ранения брюшной полости в 35-50% случаев не сопровождаются повреждени-ем органов [15][16][17][18][19][20][21][22][23][24][25][26][27]. В то же время после эксплора-тивной лапаротомии возможны опасные для жизни осложнения: спаечная кишечная непроходимость, психозы, пневмонии, гнойные осложнения, а в позд-ние сроки послеоперационные грыжи [22][23][24].…”
unclassified